Development of the "Busui Ceria" animation video application for pregnant women and breastfeeding mothers - Virgian, Kharisma; Setiawati, Desy (Science Midwifery, 2025)
Breastfeeding is the process of providing nutrition in the form of breast milk (breast milk) to the baby. This process is the physiological phase of a woman when she begins to experience pregnancy and gives birth to a baby. In order for the breastfeeding process to run smoothly, mothers must start preparing for it from the beginning of pregnancy. One of the most important factors that mothers should prepare for is knowledge about breastfeeding. To increase maternal insight and knowledge about breastfeeding, an educational medium is needed. Objective: This study aims to develop breastfeeding education media in the form of animated videos for pregnant and lactating women. Research Method: The method used in this study is the Research and Development Method with the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model. Research results: The one-to-one test from 3 respondents obtained a percentage of 99.5% with Very Good qualifications, the Small Group Test from 10 respondents obtained a percentage of 92% with Very Good qualifications, the Field Group Test from 30 respondents obtained a percentage of 94.41% with Very Good qualifications, the Validation Results of the material expert obtained a score of 96.36%. With media feasibility criteria with Excellent qualifications and Validation Results, media experts received a score of 96.1% with media feasibility criteria with Excellent qualifications. With animated videos, health workers can use educational media that are more effective, innovative, and attractive for pregnant and lactating women.